Extraskeletal Osteosarcoma of Penis: A Case Report - Wu, Chuan-zhen; Li, Cheng-mei; Han, Song; Wu, Shuang (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Extraskeletal osteosarcoma (EOS) is rare and commonly arises in the retroperitoneum, limbs, head and neck. There is no significant difference between EOS and other malignant tumors in soft tissue. Localized pain and swelling are the common presenting symptoms. Clinical diagnosis of EOS is difficult, imaging techniques may be helpful and careful, and the histopathological analysis is necessary. The common histological variants of EOS include: osteoblastoma, chondroblastoma, and fibroblastoma, and other unusual subtypes were reported occasionally. It should be distinguished with myositis ossificans, malignant mesenchymoma, giant cell tumor and parosteal osteosarcoma. We present an EOS arising in the penis. The primary site and histological category of the tumor were extremely rare. We hope the case will be helpful to the recognition of clinical signs, iconography and histopathology of EOS.